The Qur’anic Concept of Leadership: A Contextual Analysis of the Intertextual Relationship among Qur’anic Verses on Leadership - Hadiyan; Muhammad Choirin; Laila Yumna; Muhammad Hafizul Ilmi (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2026)
This article examined the concept of leadership in the Quran, focusing on the word caliph, which appears twice: in Surah Al-Baqarah, verse 30, and Surah Sad, verse 26. In Surah Al-Baqarah, the word caliph refers to Adam, whom Allah endowed with knowledge, whereas in Surah Sad, it refers to David, whom Allah commanded to rule in justice. Both keywords, knowledge and justice, align with the teachings of Surah Al-Ahzab, which emphasize that the divine trust inherently entails leadership. Surah Al-Ahzab describes humanity that undertook this trust as unjust and ignorant. Based on these three surahs, leadership in the Quran holds a unique characteristic: it defines a leader as a human being who must possess knowledge for self-guidance and embody justice when governing others. Another characteristic is that a leader must avoid the opposites of these qualities: ignorance and injustice.